Evaluation of adalimumab effects on left ventricle performance by echocardiography indexes among patients with immunosuppressant refractory ulcerative colitis - Hatamnejad, Mohammad Reza; Karvandi, Mersedeh; Jodatfar, Fateme; Ebrahimi, Nastaran; Shojaeian, Fatemeh; Baradaran Ghavami, Shaghayegh; Balaii, Hedieh; Moeeni, Mahdi; Rajabnia, Mohsen; Shahrokh, Shabnam; Asadzadeh Aghdaei, Hamid (Frontiers in Medicine, 2023)
Background and aims Inflammatory bases lead to a simultaneous flourishing of cardiovascular complications with inflammatory bowel disease (IBD). As a released cytokine, tumor necrosis factor-α (TNF-α) can either disrupt or preserve cardiovascular performance. Due to this controversy, this study aimed to appraise the short-term anti-TNF (adalimumab [ADA]) relics on cardiac function by gauging the echocardiography indexes in patients with immunosuppressant refractory ulcerative colitis (UC). Methods All cases with a definite diagnosis of UC were included based on providing written informed consent and owning the severe form of active disease (Mayo score ≥7), which did not dampen with immunosuppressant. Patients were excluded in the case of previous cardiac ailments/risk factors and prior related surgical or pharmaceutical intervention. Transthoracic echocardiography (TTE) was carried out before and 3 months after biological regimen allocation and changes in indexes [ejection fraction (EF), left ventricular end-diastolic volume (LVEDV)/left ventricular end-systolic volume (LVESV), and global longitudinal strain (GLS) in standard parasternal short axis from mid-ventricular level, two-, three-, and four-chamber apical long axes] were compared via statistical analyses. Results The study consisted of 13 (65%) men and 7 (35%) women, with a mean age of 36.54 ± 11.3 years. Participants mainly possessed Montreal class I (45%) and an average of 3.25 years of disease duration. The intervention significantly controlled inflammation [endoscopic Mayo score (P = 0.001), partial Mayo score (P = 0.001), and C-reactive protein (P = 0.001)]. Endoscopic and clinical remission was obtained in 7 (35%) and 9 (45%) patients, respectively; however, no significant discrepancy related to the LVEDV (P = 0.86), LVESV (P-value = 0.25), EF (P-value = 0.06), and GLS in standard parasternal short axis (P = 0.73), long axis [apical 2-chamber (P-value = 0.61), apical 3-chamber (P-value = 0.15), and apical 4-chamber (P-value = 0.19) views] was observed before and after the intervention. Furthermore, no statistically significant correlation between disease activity and cardiac function was found, neither before nor after ADA administration. Conclusion The present perusal found no deterioration in left ventricular function indexes with ADA intervention among patients with IBD without cardiac ailment. Thus, prescribing the anti-TNF to alleviate the inflammation can be carried out with less concern about cardiac consequences and considering other adverse traces in the target group.